2002
DOI: 10.1056/nejmoa021437
|View full text |Cite
|
Sign up to set email alerts
|

Mercury and the Risk of Coronary Heart Disease in Men

Abstract: Our findings do not support an association between total mercury exposure and the risk of coronary heart disease, but a weak relation cannot be ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
197
3
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 280 publications
(208 citation statements)
references
References 23 publications
7
197
3
1
Order By: Relevance
“…The levels of mercury found in our study were comparable to a similarly designed, recent study using ''control'' participants in eight European studies (Guallar et al, 2002) but lower than many early other studies (Suzuki et al, 1989;Garland et al, 1993;MacIntosh et al, 1997;Mortada et al, 2002;Yoshizawa, 2002;Joshi et al, 2003, p. 4). Temporal trends are one possible explanation; however, a larger study would be necessary to identify such trends in mercury levels.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The levels of mercury found in our study were comparable to a similarly designed, recent study using ''control'' participants in eight European studies (Guallar et al, 2002) but lower than many early other studies (Suzuki et al, 1989;Garland et al, 1993;MacIntosh et al, 1997;Mortada et al, 2002;Yoshizawa, 2002;Joshi et al, 2003, p. 4). Temporal trends are one possible explanation; however, a larger study would be necessary to identify such trends in mercury levels.…”
Section: Discussionsupporting
confidence: 78%
“…Temporal trends are one possible explanation; however, a larger study would be necessary to identify such trends in mercury levels. In one of these studies, median fish intake reported for each quintile of toenail mercury concentration ranged from 21 to 51 g/day (Yoshizawa et al, 2002), compared with overall medians in our study of 25 g/day for fin fish and an additional 8 g/day of shellfish. The mean mercury toenail concentration in that study was 0.45 mcg/g among participants without occupational exposure, compared with 0.27 mcg/g in ours.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…[9] Although inconclusive, recent studies have suggested that MeHg may promote or predispose to the development of heart disease. [10,11] Increased MeHg exposure was associated with adverse cardiovascular effects in adults [12][13][14] and children. [15] This paper reviews the human MeHg toxicology and the effects of MeHg exposure on neurobehavioural and cardiovascular outcomes, as based on human evidence from epidemiologic data.The paper also discusses issues in regard to exposure assessment and imprecision, and the relationship between the benefits from nutrients in fish and the risks associated with MeHg toxicity.…”
Section: Dr Grandjean Is Professor and Chair Of Environmental Medicinmentioning
confidence: 99%
“…Studies of the cardiovascular effect of Hg have used Hg levels in toenails and fingernails as biomarkers of Hg exposure, [11,55] although the extent that these reflect organic or inorganic Hg exposure is unclear. The fact that dentists have increased toenail Hg concentrations [11] would suggest that this biomarker reflects not only MeHg exposure.…”
Section: New Zealandmentioning
confidence: 99%